A Confirmatory Method Based on HPLC-MS/MS for the Detection and Quantification of Residue of Tetracyclines in Nonmedicated Feed - Rosa E. Gavilán; Carolina Nebot; Maria Veiga-Gómez; Paula Roca-Saavedra; Beatriz Vazquez Belda; Carlos M. Franco; Alberto Cepeda (Journal of Analytical Methods in Chemistry)
The Commission Regulation 574/2011/EC set up maximum levels of coccidiostats and histomonostats in nonmedicated feed as a consequence of carry-over during manufacturing. Carry-over takes place from medicated to nonmedicated feed during feed production. Similar contamination could also occur for other pharmaceuticals such as tetracyclines, a group of antibiotics commonly employed in food production animal. The objective of this work is to present a simple and fast method for the simultaneous detection of four tetracyclines (chlortetracycline, doxycycline, oxytetracycline, and tetracycline) in nontarget feed at a μg/kg level. Validation of the method was performed according to the guideline included in the Commission Decision 2002/657/EC for official method. The validated method was successfully applied to 50 feed samples collected from different milk farms and 25 samples obtained from feed manufacturers. While oxytetracycline was the tetracycline most frequently detected, chlortetracycline was the analyte measured at the highest concentration 15.14 mg/Kg. From 75 nonmedicated feed analysed 15% resulted to be positive for the presence of one tetracycline.